PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS APLIKASI BOOK CREATOR PADA TEMA PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP KELAS III SD - Ayuni, Amanda Putri; fadlan, muhammad noer (Joyful Learning Journal, 2023)
This research is a type of development research (research and development) with reference to the 4D model which is an extension of Define, Design, Development and Dissemination. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative. The development of teaching materials is carried out in several stages. In the initial stage, researchers chose the material based on the Core Competencies (KI), Basic Competencies (KD), and textbooks for third grade elementary school students on the theme of growth and development of living things. After selecting the material to be developed, then make the design of Book creator learning teaching materials. Book creator learning teaching materials that have been completed are then validated by teaching material experts, material experts and teacher responses. The results of teaching material validation obtained a percentage of 100%. The results of material validation obtained a percentage of 74%. The results of teacher response validation obtained a percentage of 98%. This percentage includes very valid criteria (very feasible) to be used as teaching materials in learning activities for grade III elementary school students on the theme of growth and development of living things.